From Croatian into Latin in 1510: Marko Marulić, Regum Delmatie atque Croatie gesta - Jovanović, Neven (2010)
In 1510 Marko Marulić (Marcus Marulus, 1450–1524), a humanist from the Dalmatian city of Split, translated from Croatian into Latin the so-called Hrvatska kronika (Croatian Chronicle). This is an excerpt from the Annals of the Priest of Doclea, a medieval and for the most part legendary origo gentis of the Slavs of Dalmatia. As the Annals were originally composed in Latin, the Croatian Chronicle was itself a translation (though Marulić did not know this). Marulić gave his version the title Regum Delmatię atque Croatię gesta, and in the preface made it clear that he aimed at a wider audience (“res… quam non solum nostrę uernaculę linguę gnari, sed etiam Latinę intelligant”). But there was a problem. For this task a verbum verbo reddere approach was simply not acceptable, because the resulting text would not have met the standards of humanist Latin. Therefore, if we compare the version Marulić made with its Croatian source, as well as with the Latin Urtext, we shall better understand what was necessary for an elegant literary Latin around 1500.